The uniqueness of flow in probing the aggregation behavior of clinically relevant antibodies. Issue 5 (15th March 2020) - Willis, Leon F.; Kumar, Amit; Jain, Tushar; Caffry, Isabelle; Xu, Yingda; Radford, Sheena E.; Kapur, Nikil; Vásquez, Maximiliano; Brockwell, David J.
Abstract: The development of therapeutic monoclonal antibodies (mAbs) can be hindered by their tendency to aggregate throughout their lifetime, which can illicit immunogenic responses and render mAb manufacturing unfeasible. Consequently, there is a need to identify mAbs with desirable thermodynamic stability, solubility, and lack of self‐association. These behaviors are assessed using an array of in silico and in vitro assays, as no single assay can predict aggregation and developability. We have developed an extensional and shear flow device (EFD), which subjects proteins to defined hydrodynamic forces which mimic those experienced in bioprocessing. Here, we utilize the EFD to explore the aggregation propensity of 33 IgG1 mAbs, whose variable domains are derived from clinical antibodies. Using submilligram quantities of material per replicate, wide‐ranging EFD‐induced aggregation (9‐81% protein in pellet) was observed for these mAbs, highlighting the EFD as a sensitive method to assess aggregation propensity. By comparing the EFD‐induced aggregation data to those obtained previously from 12 other biophysical assays, we show that the EFD provides distinct information compared with current measures of adverse biophysical behavior. Assessing a candidate's liability to hydrodynamic force thus adds novel insight into the rational selection of developable mAbs that complements other assays. Abstract : The development of therapeutic monoclonal antibodies (mAbs) can be hindered by their tendency to aggregate throughout their lifetime. We have developed an extensional and shear flow device (EFD), which subjects proteins to defined hydrodynamic forces which mimic those experienced in bioprocessing. Here, by comparing the flow‐induced aggregation data to those obtained previously from 12 other biophysical assays, we show that extensional flow provides distinct information compared with current measures of adverse biophysical behavior.